Video production techniques : theory and practice from concept to screen - Diefenbach, Donald L., 1967-; Slatton, Anne E. (New York Routledge, 2020)
"Video Production Techniques is an essential guide to the art and craft of video production. It introduces students to the theoretical foundations as well as the practical skills needed to make a successful video project. The opening chapter introduces the reader to the language of motion pictures and sets the stage for effective visual storytelling. Unit I guides students through the theory, techniques, and processes of writing, shooting, and editing video productions. Unit II expands on these basic principles to explore the crafts of sound recording/design, lighting, and directing. Unit III surveys the industries, formats, and methods for creating fiction and nonfiction programs. The final unit of the text examines options for distribution and career opportunities in video production. Newly updated and revised, the second edition of Video Production Techniques unifies theory and practice for instructors and students. It is a great tool for use in introductory-level video production courses and for the independent learner. The accompanying Companion Website features Instructor Resources including a sample syllabus, quiz bank, sample assignments, and PowerPoint slides for each chapter, alongside illustrative video demonstrations for students."--
Includes bibliographical references and index.
Keywords: Video recordings -- Production and direction